EFFECT OF ASSOCIATION BRAND, QUALITY PRODUCTS / SERVICES AND PROMOTION OF AWARENESS THROUGH MUSLIM HALAL CONSUMER CONFIDENCE BRAND J.CO DONUTS AND Breadtalk - Aria Wahyudi, Muhammad (Dinasti International Journal of Digital Business Management, 2020)
Along with the growing Muslim population in Indonesia has increased the potential for halal products were great, the context of the recognition of halal food needs to be examined further. Halal products should be recognized as a symbol of cleanliness, safety, and high quality for Muslim consumers (Merican, 1995). Until now though there is plenty of halal food and many research reports about the halal food market, but the study of the theory of purchasing kosher food is very rare (Natural & Suyuti, 2011). To boost economic growth through the development of halal products, it must know the level of awareness in Indonesia Muslim behavior as consumers of halal products. Awareness is the ability to perceive an event as well as the object, which implies the concept of understanding and perception of the event or subject. In a promotional message to shape perceptions and consumer confidence, the promotional messages tailored to the intended target market and the moment or timing. The brand promotion that is directed to the target market will very influence awareness Muslim Halal consumer perception of the brand or the product. Hereinafter Process author, execute collection primary data related to Halal Awareness and Brand Trust for Muslim respondents younger age (18 years to 35 years), with a predominance of middle class living in Jakarta and surrounding areas. This initial survey for identifying problems Halal Awareness and Brand Trust of 70 respondents then customized promotional messages to the intended target market and the moment or timing.